Strategies for strengthening small-scale food processing in Eastern and Southern Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Strategies for strengthening small-scale food processing in Eastern and Southern Africa Proceedings of a workshop, held in 1998 in Entebbe, Uganda. CTA, 2000. 100 pp. ISBN 92 9081 2338 CTA number 1019. 10 credit points